The Use of ChatGPT in Lectures: Student Perceptions Reviewed from the Aspects of Utilization, Digital Literacy, and Academic Ethics - Farakh Lisda Aulia; Sony Zulfikasari (Jurnal Penelitian Pendidikan, 2026)
The development of Artificial Intelligence (AI), especially ChatGPT, has brought changes in the learning process in universities and encouraged students to utilize technology to support academic activities. This condition makes it important to find out how students perceive the use of ChatGPT in lectures. This study aims to analyze students' perception of the use of ChatGPT from the aspects of utilization, digital literacy, and academic ethics. This study uses a survey method with a quantitative descriptive approach. Data was collected through an online questionnaire using Google Form to students of the Educational Technology Study Program, Faculty of Education and Psychology, Semarang State University, class of 2022–2025 who were selected using random sampling techniques. The research instrument was in the form of a closed questionnaire with a five-point Likert scale, while the data was analyzed using descriptive statistics through the calculation of mean and percentage. The results of the study show that students have a very positive perception of the use of ChatGPT in lecture activities, which is reflected in the aspects of utilization, digital literacy, and academic ethics. These findings show that ChatGPT is seen as a technology that is able to support the learning process if used wisely, accompanied by digital literacy skills, and still paying attention to academic ethics. This research contributes to enriching the study of the use of AI in higher education and can be a reference for the development of learning that integrates AI effectively and responsibly.